Feeding problems reported by parents of young children with type 1 diabetes on insulin pump therapy and their associations with children’s glycemic control - Patton, Susana R. (2009)
OBJECTIVE: Previous research demonstrated high rates of perceived mealtime behavior problems in families of young children with type 1 diabetes who were managed with conventional therapy. Due to new insulin regimens that offer greater flexibility, re-examination of mealtime behaviors is required. We assessed parent-reported mealtime behaviors in a sample of young children using an insulin pump. An additional aim evaluated the associations of two measures of parental feeding behavior with children’s glycemic control. METHODS: Primary caregivers of 31 young children (M age= 5.0 ± 1.3 years) completed the Child Feeding Questionnaire (CFQ) and the Behavioral Pediatric Feeding Assessment Scale (BPFAS). Hemoglobin A1c (HbA1c) was used as a surrogate marker for children’s glycemic control. RESULTS: Children had a mean HbA1c of 7.8% ± 0.64. Mean CFQ Restriction and Pressure to Eat scores were M= 3.1 ± 0.94 and M= 2.0 ± 0.88, respectively (range= 1-5). Mean BPFAS Parent and Child scores were 16.0 ± 4.3 (range= 10-50) and 44.9 ± 9.3 (range= 25-125), respectively. Positive correlations were found between children’s HbA1c levels and caregivers’ reporting of frequency of child mealtime behavior problems. CONCLUSIONS: Caregivers of young children on pump therapy report relatively low rates of mealtime behavior problems. However, correlations with children’s HbA1c suggest parent-child mealtime behaviors continue to relate to children’s health outcomes. Research is needed to determine if changing mealtime interactions can improve children’s glycemic control; items from the BPFAS and CFQ can offer targets to guide interventions.